Cost comparison of different models of palliative care delivery. (23rd September 2020) - Comans, Tracy; Nguyen, Kim‐Huong; Stafford‐Bell, Fiona; Agar, Meera
Abstract: Objective: The aim of this project was to assess the value for money of a modified unit within a residential aged care facility (RACF) for people requiring palliative care at the end of life. Methods: A three‐way comparison using a mixed‐method costing was used to estimate the per day cost of the unit compared to care in a palliative care unit within a hospital and a standard RACF bed. Results: The cost of the unit was estimated at $242 per day (2015 Australian dollars). The palliative care hospital bed cost $1, 664 per day. The cost of a standard RACF bed was $123 per day, indicating that an additional $120 per day is required to provide the higher level of care required by people with complex palliative care needs. Conclusion: A modified RACF unit could provide substantial cost savings to the health budget for selected complex palliative care patients.